2018
DOI: 10.1111/cen.13899
|View full text |Cite
|
Sign up to set email alerts
|

Relation between hysterectomy, oophorectomy and the risk of incident differentiated thyroid cancer: The E3N cohort

Abstract: Summary Background Thyroid cancers are threefold more frequent in women than in men. A role of reproductive or hormonal factors has been suggested but with contradictory results. We investigated potential associations between history of hysterectomy, with or without oophorectomy, and history of benign gynaecological disease (uterine fibroids, endometriosis) and the incidence of differentiated thyroid cancer, in a large French prospective cohort. Methods A total of 89 340 women from the E3N cohort were followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 41 publications
2
20
0
2
Order By: Relevance
“…Guenego et al found that women with a history of UF, irrespective of whether they had a hysterectomy or not, were at a higher risk of thyroid cancer (HR: 1.91; 95% CI: 1.50-2.44). When they considered history of UF and hysterectomy simultaneously, each variable remained statistically associated with the risk of thyroid cancer in the same multivariate statistical model [hysterectomy (yes/no): HR: 1.70, 95% CI: 1.27-2.28; UF (yes/no): HR: 1.33, 95% CI: 1.01-1.75] [13]. Luo et al, indicated that women who had undergone a hysterectomy had a significantly increased risk of thyroid cancer when compared with women who had not undergone a hysterectomy (HR: 1.46, 95% CI: 1.16-1.85) [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guenego et al found that women with a history of UF, irrespective of whether they had a hysterectomy or not, were at a higher risk of thyroid cancer (HR: 1.91; 95% CI: 1.50-2.44). When they considered history of UF and hysterectomy simultaneously, each variable remained statistically associated with the risk of thyroid cancer in the same multivariate statistical model [hysterectomy (yes/no): HR: 1.70, 95% CI: 1.27-2.28; UF (yes/no): HR: 1.33, 95% CI: 1.01-1.75] [13]. Luo et al, indicated that women who had undergone a hysterectomy had a significantly increased risk of thyroid cancer when compared with women who had not undergone a hysterectomy (HR: 1.46, 95% CI: 1.16-1.85) [14].…”
Section: Discussionmentioning
confidence: 99%
“…Because the occurrence of both UF and thyroid cancer may be related to female hormones, some studies have explored the link between the two diseases and have found that women with a history of UF had a significantly increased risk of thyroid cancer [8,13]. Moreover, researchers also investigated the relationship between hysterectomy and thyroid with inconclusive results [13][14][15]. Through a nationwide database, we designed this study to determine whether Taiwanese women with UF have an increased risk of subsequent thyroid cancer and whether the history of myomectomy affects this possible relationship.…”
Section: Introductionmentioning
confidence: 99%
“…In patients diagnosed with thyroid cancer, the age at initial diagnosis was lower among women with than women without hysterectomy, but survival rates did not differ [44]. Findings from a large, prospective, cohort study in France showed a twofold increased risk of thyroid cancer among women with hysterectomy (n = 80,197) compared with those without (n = 9143) (aHR 2.05; 95% CI 1.65 to 2.55) [42]. This study also showed that a history of fibroids was associated with an increased risk of thyroid cancer (aHR 1.91; 95% CI 1.50 to 2.44), even when adjusted for hysterectomy, leading authors to conclude that further examination is required to determine any shared mechanisms between UF and thyroid cancer.…”
Section: Impact Of Hysterectomy On Cancer Riskmentioning
confidence: 96%
“…These findings suggest that there may be an association between hysterectomy and an increased risk of certain types of cancer, notably thyroid cancer, RCC, bladder cancer, and urinary tract cancer [41][42][43][44]. It is important to acknowledge the potential biases in these studies in that the underlying condition leading to hysterectomy (e.g., obesity, abnormal uterine bleeding, or exposure to ionizing radiation) may be associated with these cancers; therefore, the women included in the studies may be predisposed to them.…”
Section: Impact Of Hysterectomy On Cancer Riskmentioning
confidence: 97%
“…У лонгітюдному дослідженні, яке охопило 89 340 жінок із епідеміологічного дослідження The E3N Cohort (почалось у 1990 р. з метою вивчення факторів ризику онкологічних захворювань у жінок, які були застраховані через французьку національну систему охорони здоров'я, що в першу чергу охоплювала вчителів), A. Guenego et al виявили підвищені ризики розвитку РЩЗ в жінок із обтяженим гінекологічним анамнезом. Так, жінки з лейоміомою матки мали підвищений ризик розвитку РЩЗ в 1,91 раза, а в жінок, яким було проведено гістеректомію з приводу лейміоми матки або ендометріозу, цей ризик збільшувався у 2,05 раза [32].…”
Section: етіологія рщзunclassified